Love and Other Flights – Legal Subtexts and the Law as a Strategy of Reader Guidance in Bernhard Schlink's Liebesfluchten. Issue 2 (3rd May 2016) - Stürmer, Franziska; Meier, Patrick
Abstract: This article investigates the importance Bernhard Schlink's profession as a lawyer bears on his writing concerning both content and style. In an exemplary analysis of three of his stories – "Girl with Lizard, " "A Little Fling, " and "The Other Man" (all published in Flights of Love, 2002) – it will become evident how Schlink addresses legal issues and makes use of legal philosophical problems as well as strategically playing out legal rhetoric to bring home his message: let bygones be bygones. Thus, although his stories appear to start out as narrative investigations into a problematic (German) past, they eventually turn out to be a series of flights from confrontation with this past.